2018
DOI: 10.24843/jh.2018.v22.i02.p14
|View full text |Cite
|
Sign up to set email alerts
|

English Compound Adjective with Special Reference to Tourism Website

Abstract: The study entitled English Compound Adjective with Special Reference to Tourism Website aims to analyze the constructions of compound adjectives found in Tourism website, explaining their syntactic functions and meaning. The data were taken from several tourism websites on internet, they are, Discover Hong Kong, Wonderful Indonesia, Italian Tourism Official Website, and Visit the USA. Firstly, the tourism websites were accessed and website pages were printed. Secondly, the website pages that had been printed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The next prior study is an article done by Sari (2018) entitled "English Compound Adjective with Special Reference to Tourism Website." The aims of this study are to analyze the constructions of compound adjectives found in Tourism website and explain their syntactic functions as well as their meaning.…”
Section: Introductionmentioning
confidence: 99%
“…The next prior study is an article done by Sari (2018) entitled "English Compound Adjective with Special Reference to Tourism Website." The aims of this study are to analyze the constructions of compound adjectives found in Tourism website and explain their syntactic functions as well as their meaning.…”
Section: Introductionmentioning
confidence: 99%